Essential Oil of Fractionated Oregano as Motility Inhibitor of Bacteria Associated with Urinary Tract Infections - Eduardo Sánchez García; Cynthia Torres-Alvarez; Elías G. Morales Sosa; Mariana Pimentel-González; Licet Villarreal Treviño; Carlos Abel Amaya Guerra; Sandra Castillo; José Rodríguez Rodríguez (MDPI AG, 2024)
In this research, several analyses were carried out on concentrated fractions of Mexican oregano essential oil (Poliomintha longiflora Gray) in order to determine its ability to inhibit the growth and the motility of Escherichia coli (swimming), Pseudomonas aeruginosa (swimming), and Proteus vulgaris (swarming); these Gram-negative bacteria associated with urinary tract infections are motile due to the presence of flagella, which is considered an important virulence factor that favors their motility when trying to reach the target organ and cause an infection. Also, the resistance pattern to antibiotics of each strain was determined. The results showed resistance pattern (8 out of 12 antibiotics tested) for P. aureginosa, while E. coli and P. vulgaris were resistant to 4 antibiotics out of the 12 tested. On the other hand, fractionated oregano caused an inhibition of growth and a reduction in motility, varying between fractions and among bacteria. Fraction 4 showed major growth reduction, with MBC values ranging from 0.002 to 23.7 mg/mL. Treatment with fractionated oregano (F1, F2, F3, F4) reduced the motility by 92-81% for P. vulgaris, 90-83% for E. coli, and 100-8.9% for P. aeruginosa. These results demonstrated a higher performance with a lower application dose due to its high content of Carvacrol and Thymol; unlike other concentrated fractions, this synergy of oxygenated monoterpenes may cause greater antimicrobial activity.